Tourism accommodation and economic contribution on the Ningaloo Coast of Western Australia - Wood, David; Hughes, Michael (Routledge Taylor and Francis, 2006)
The Ningaloo Coast of Western Australia is a popular nature-based tourism destination. Key locations within the region have had to cope with tourist populations that far outstrip the residential population during peak season, injecting much needed revenue into the local economy while putting a huge strain on local infrastructure and the environment. Accommodating the large number of seasonal tourists has proved to be a challenge in terms of maximizing benefits while minimizing costs. The type of accommodation used by these tourists can have a significant influence on the costs and benefits of tourism to the region. This paper uses longitudinal visitor survey data to examine the economic contribution of tourists to the region based on their accommodation preference. Tourists using unmanaged remote camping facilities contributed the least in direct spend to the local economy while those staying in motels contributed the most. Unmanaged camping arguably incurs greater costs in terms of impacts on the natural environment. Implications for further development in the region are discussed.